PENGARUH MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN APLIKASI WORDWALL TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD INPRES MALENGKERI II - Nur Fitria Ningsih; Nasrun; Ernawati (STKIP Subang, 2025)
The main problem in this study is whether the Teams Games Tournament (TGT) learning model supported by the Wordwall application has an effect on the mathematics learning outcomes of fourth-grade students at SD Inpres Malengkeri II. This study aims to determine the effect of the Teams Games Tournament (TGT) learning model supported by the Wordwall application on the mathematics learning outcomes of fourth-grade students at SD Inpres Malengkeri II.The study used a quantitative approach with a quasi-experimental method and a non-equivalent control group design. The sample consisted of classes IV A (control) and IV B (experimental) with a total of 50 students. The instruments consisted of pretest-posttest questions and observation sheets. Data were collected through tests and observations, analyzed descriptively and inferentially.The results showed a posttest average of 85.28 for the experimental class and 76.84 for the control class. The t-test showed a significance of 0.009 (<0.05), indicating that the implementation of TGT with the help of Wordwalls had a significant effect on students' mathematics learning outcomes.